The main elements of the solution to China’s demotic violence - Yin Xuan (SHS Web of Conferences, 2024)
Domestic violence represents a complex and pervasive issue within China, deeply entrenched in historical norms and sociocultural attitudes. Even with legal reforms aimed at criminalizing domestic violence and establishing legal protections for victims, challenges persist due to the societal perception of domestic violence as a family matter. This paper critically examines the main elements necessary for effectively combating domestic violence in China—policy instruments, policy implementation, and lobbying. By dissecting the shortcomings of current measures, the paper argues for the adoption of multidimensional policy tools beyond policing and legal action, such as public awareness campaigns and persuasive strategies designed to shift societal attitudes. The significance of rigorous policy implementation is emphasized, highlighting the need for iterative enforcement and organizational learning to ensure the efficacy of domestic violence policies. Furthermore, the complex role of lobbying within China's political context is explored, demonstrating its impact on policy proposals and reforms. Overall, the paper posits the need for a comprehensive approach, involving a concerted effort from policymakers, law enforcement, and civil society to address the multifaceted challenges of domestic violence in China.